A fiber-reinforced thermoelastic medium with an internal heat source due to hydrostatic initial stress and gravity for the three-phase-lag model. Issue 1 (12th June 2017) - Said, Samia M.
Abstract : Purpose: The purpose of this paper is to investigate the effect of a hydrostatic initial stress and the gravity field on a fiber-reinforced thermoelastic medium with an internal heat source that is moving with a constant speed. Design/methodology/approach: A general model of the equations of the formulation in the context of the three-phase-lag model and Green-Naghdi theory without energy dissipation. Findings: The exact expressions for the displacement components, force stresses, and the thermal temperature for the thermal shock problem obtained by using normal mode analysis. Originality/value: A comparison made between the results of the two models for different values of a hydrostatic initial stress as well as an internal heat source. Comparisons also made with the results of the two models in the absence and presence of the gravity field as well as the reinforcement.